2006
DOI: 10.1158/1541-7786.mcr-06-0056
|View full text |Cite
|
Sign up to set email alerts
|

Tuberin Nuclear Localization Can Be Regulated by Phosphorylation of Its Carboxyl Terminus

Abstract: Tuberin, the tuberous sclerosis 2 (TSC2) gene product, has been identified as a tumor suppressor protein genetically implicated in the pathology of tuberous sclerosis and the female-specific lung disease lymphangioleiomyomatosis. Tuberin and its predominant cytoplasmic binding partner hamartin have been shown to complex with a variety of intracellular signaling regulators and affect the processes of protein translation, cellular proliferation, cellular migration, and cellular transcription. In previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…Previous studies from our laboratory and that of others have demonstrated that tuberin can directly impact ERmediated genomic and nongenomic signaling [39][40][41][42]. Cumulatively these data support the hypothesis that, if ER is present in a cell, disruption of tuberin/hamartin-associated signaling events can directly impact signaling pathways mediated by ER .…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies from our laboratory and that of others have demonstrated that tuberin can directly impact ERmediated genomic and nongenomic signaling [39][40][41][42]. Cumulatively these data support the hypothesis that, if ER is present in a cell, disruption of tuberin/hamartin-associated signaling events can directly impact signaling pathways mediated by ER .…”
Section: Introductionsupporting
confidence: 84%
“…In the LAM-associated cell lines examined in these studies it was observed that transcription expression of the ER gene was actively being initiated from multiple ER promoters. Although these studies were limited to looking at steadystate levels of ER mRNA and therefore do not directly address transcription rates, our previously published studies demonstrating tuberin's ability to localize to the nucleus [40,42] and tuberin's ability to directly impact transcription regulation [30,41] would support a direct impact on ER mRNA transcription as opposed to ER mRNA degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17) Heat shock resulted in activation of Akt, as indicated by modulation of Ser308, and was accompanied by phosphorylation of tuberin at Thr1462 (Fig. 4A).…”
Section: Phosphorylation Of Akt and Tuberin Is Dependent On The Hamarmentioning
confidence: 97%
“…Segundo Soucek et al (1997), o complexo hamartina-tuberina pode regular negativamente a progressão do ciclo celular deixando-as em um estado quiescente G0/G1 ao antagonizar mTOR ou por ter a capacidade de interagir diretamente no núcleo com p27/p27 KIP1 impedindo a degradação ou ubiquitinação desta última. Tuberina é capaz de transitar entre o citoplasma celular (onde interage com a hamartina) e o núcleo celular quando há fosforilação de sua porção carboxi-terminal (resíduos 1351 e 1807, Lou et al, 2006;York et al, 2009). Essa redistribuição na fase tardia de G1 do ciclo celular, demonstrada em nossos dados, já foi evidenciada em linhagem celular de músculo liso de traqueia (Clements et al, 2007) e outras (Rosner et al, 2004).…”
Section: Discussionunclassified